2015
DOI: 10.1128/aem.02817-14
|View full text |Cite
|
Sign up to set email alerts
|

Immunoprecipitation of Native Botulinum Neurotoxin Complexes from Clostridium botulinum Subtype A Strains

Abstract: Botulinum neurotoxins (BoNTs) naturally exist as components of protein complexes containing nontoxic proteins. The nontoxic proteins impart stability of BoNTs in the gastrointestinal tract and during purification and handling. The two primary neurotoxin complexes (TCs) are (i) TC1, consisting of BoNT, nontoxin-nonhemagglutinin (NTNH), and hemagglutinins (HAs), and (ii) TC2, consisting of BoNT and NTNH (and possibly OrfX proteins). In this study, BoNT/A subtypes A1, A2, A3, and A5 were examined for the composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…In several studies, no stable complex of BoNT/ A2 with any OrfX-protein has been found. Only the M-PTC consisting of BoNT and NTNH has been identified [2,26,52]. This was also the case in this study using recombinant proteins (Fig.…”
Section: Orfx Cluster General Discussionsupporting
confidence: 74%
“…In several studies, no stable complex of BoNT/ A2 with any OrfX-protein has been found. Only the M-PTC consisting of BoNT and NTNH has been identified [2,26,52]. This was also the case in this study using recombinant proteins (Fig.…”
Section: Orfx Cluster General Discussionsupporting
confidence: 74%
“…2A). High molecular complexes from Pbm were concentrated 21 and the sample, which contained PMP1 and Cry16A (Supplementary Fig. 2B), was separated by native PAGE, subjected to analysis by ultra-performance liquid chromatography-tandem mass spectrometer (UPLC/MS/MS), and compared with a similar extracted fraction from the Pbm∆109 mutant (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pb malaysia and Pbm∆109 proteins present in the culture supernatant were acid precipitated adding H 2 SO 4 dropwise to pH 3.5 as described 21 . Precipitated proteins were extracted by agitation for 2 h in 0.1 M sodium citrate buffer pH 5.5 and analyzed in native protein acrylamide gels.…”
Section: Methodsmentioning
confidence: 99%
“…In strain IBCA10-7060/CDC69016, the bont /B2 gene is arranged in an ntnh-ha toxin gene cluster encoding nontoxic nonhemagglutinin and three hemagglutinins (HAs), whereas the BoNT/FA gene is arranged in an ntnh-orfX cluster encoding NTNH, P47, and putatively three ORFX proteins ( 23 ). It has previously been shown that immunoprecipitation of BoNTs with OrfX gene clusters detected only the full-length NTNH in association with the BoNT but not the OrfX proteins, whereas the BoNTs from HA gene clusters contained the NTNH and HA proteins ( 45 ). Thus, the association of BoNT/FA with only NTNH and the elution of the HA proteins in a separate fraction ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For immunoprecipitation analysis, culture supernatants of strain CDC69016/B2tox − were analyzed as described previously ( 45 ). Briefly , polyclonal antibodies raised against BoNT/A1 or BoNT/B1 ( 49 ) were used for immunoprecipitation of the respective toxins from 1 ml of culture supernatants.…”
Section: Methodsmentioning
confidence: 99%